Analysis of the relationship between practicing adapted sports physical activity and accepting disability (a psychological approach) - AMAR RAOUAB (Social Sciences Journal, 1970)
This study aimed, as it was previously shown to us, to analyze the relationship between the practice of adapted sports physical activity and acceptance of disability, among the sample distributed into two categories, the category of wheelchair basketball practitioners in Algerian clubs, and the category that does not practice adapted sports physical activity located in vocational training centers For the category of the disabled. This study yielded the following results: - The higher the age, the greater the acceptance of the disability for the disabled - The more the disability is acquired, the better the acceptance of the disability - The higher the educational level, the lower the degree of disability - If the disabled person does not work, the acceptance of the disability decreases - Practitioners Adapted sports activity is more accepting of disability than non-practitioners. The practitioners of the air-conditioned sporting activity got the positive effect of the environment in which they live more than the category of non-practitioners. - It was found that among the strongest factors that directly affect acceptance of disability are the independent variables (occupational status, marital status, academic level, origin of disability). - There is a weak relationship between the influence of the social environment and the acceptance of disability, that is, there is a relationship and influence on the acceptance of disability.